The Effects of Green Betel Leaf (Piper betle) Extract Eye Drops on the Number of Staphylococcus aureus Colonies in Conjunctivitis Wistar Rats Model (Rattus novergicus) - Mahira Aisyah Putri Nur; Sudaryanto Sudaryanto; Endang Sri Lestari; Erwin Kresnoadi (Faculty of Pharmacy, Universitas Gadjah Mada, 2021)
Irrational use of antibiotics can cause resistance to some diseases such as bacterial conjunctivitis caused by Staphylococcus aureus. Previous research said that green betel leaf (Piper betle) contains antimicrobial compounds such as eugenol, cavalry, tannins, saponins, and flavonoids which also have antiseptic power as well as antibiotics. This study aims to prove the decrease in the number of Staphylococcus aureus colonies after giving green betel leaf eye drops (Piper betle) to conjunctivitis Wistar rats (Rattus norvegicus). This research was true experimental with a pretest-posttest control group design. 25 male white Wistar rats as objects were selected by simple random sampling and grouped into 5 groups randomly. The rats were given Staphylococcus aureus, control group K+ was given 0.5% levofloxacin eye drops, and K- was given aquadest as a comparison. Treatment groups P1, P2, and P3 were given different concentrations of betel leaf eye drops. Swab pretest was done 3 days after the rats were inoculated with Staphylococcus aureus and swab post-test was done 5 days after the rats were given green betel leaf eye drops, the calculation of Staphylococcus aureus bacteria colonies used the Total Plate Count (TPC) method. There was a significant decrease (p<0.05) in the number of bacterial colonies for K-, K+, P1, P2, and P3 groups. In addition, there was a significant difference (p<0.05) between K+ with P1 and K+ with P3. There was a decrease in the number of Staphylococcus aureus for all groups of conjunctivitis Wistar rats (Rattus norvegicus)